Auditoría de Gestión y Control de los Procesos de Auditoría Ejecutados por la Superintendencia de Economía Popular y Solidaria Sector No Financiero, Durante el Periodo 2018. - Izquierdo Carpio, Erika Beatriz (2020)
The management audit and the internal control that is executed in the governmental entities are complementary, in this way, the internal control plays a fundamental role in orienting the directors of the governmental institutions in making informed decisions. Additionally, the control of the public and private sector started up differs from each other, however the techniques and procedures applied to execute the control are very similar, as is the State Comptroller's Office based on the processes applied in the Management audit. , proof of compliance with the organizational objectives, however in the field of cooperativism, the focus is on the decisions taken by the governing bodies, general assembly, board of directors and supervisory board; it is the assessment towards regulatory compliance, and not towards the integral evaluation of the achievement of the objectives at the cooperative level, as is the case of the management audit. For this purpose, the management audit will be analyzed as a procedural reference, for the analysis of the supervisory supervision mechanisms executed by the Superintendence of Popular and Solidarity Economy, since a weight that is controlled by private law organizations and Self-employed, some of the organizations of the EPS, have been benefited by donations, concessions and government grants, with the purpose of an improvement in the quality of life of these actors of the EPS and the achievement of their corporate purpose.